Violence and memory in two instances of representation of the world of work: The owners of the land and In the tragic week of David Viñas and Brickmakers of Selva Almada - Ferrante, Betina (Universidad Nacional del Litoral, 2022)
This paper explores the modes of representation of violence associated with the world of work in two moments of national narrative realism: the novels Los dueños de la tierra (The owners of the Land) and En la semana trágica (In the tragic week) by David Viñas, published in 1958 and 1966 respectively; and Ladrilleros (Brickmaker) of Selva Almada, from 2013. Both authors appeal in these Works to memory, both on a thematic level and as a constructive procedure, establishing the fragmentation that is characteristic of them as a mode of the story. In turn, an ideological core sustains them: how violence operates in the absence of the state. In the case of David Viñas, the army and white guards are the armed wing of the sectors of the oligarchy that shoot the worker-strikers; and in Selva Armada’s novel, the state abandonment in a distant, bordering space is the cause of a violence that operates as a vital matrix, naturalized on the one hand and, on the other, conceived as the only form of significance of existence.